Enhancement of low resolution models for real time large scale visualization - Like, Gobeawan (2010)
The latest data acquisition technology enables us to obtain huge 3D model data. To visualize the large 3D models in real time, large memory resources are required. However, an off-the-shelf PC often has limited memory compared to the size of such large models, so that the computer cannot display the model sat an interactive or real time frame rate. Real time visualization of a large model on a limited memory system can be realized using a simplified version of the model. This thesis discusses such a framework, with two main contributions in the areas of mesh stitching and silhouette refinement.